A randomized controlled trial examining the effects of intranasal oxytocin on alcohol craving and intimate partner aggression among couples. (August 2022) - Flanagan, Julianne C.; Nietert, Paul J.; Sippel, Lauren; Jarnecke, Amber M.; Kirby, Charli; Hogan, Jasara N.; Massa, Andrea A.; Brower, Jessica; Back, Sudie E.; Parrott, Dominic
Abstract: Background: While alcohol use disorder (AUD) is a well-established risk factor for intimate partner aggression (IPA), effective treatments for co-occurring AUD and IPA (AUD/IPA) are lacking. Oxytocin is one promising pharmacological candidate for AUD/IPA given its potential to modulate social behavior and attenuate alcohol use. However, emerging data suggests that oxytocin's prosocial effects are inconsistent, and a small number of studies have also found that oxytocin might have the potential to be aggressogenic. No studies have directly examined the impact of oxytocin on alcohol- or IPA-related outcomes in a dyadic context. Methods: The goal of this double-blind, randomized, and placebo-controlled trial was to examine the effects of a single dose of intranasal oxytocin (40 international units) on cue-induced alcohol craving, subjective aggression, laboratory task-based IPA, and cortisol reactivity in a sample of 100 couples ( N  = 200 individuals) with AUD and physical IPA in their current relationship. Results: There were no statistically significant differences between the oxytocin and placebo conditions for any of the primary outcomes. Conclusions: Findings suggest that a single dose of intranasal oxytocin was not efficacious in mitigating alcohol craving or aggression in this sample. Although hypotheses were not supported, the findings provide important evidence that oxytocin was not aggressogenic in this high-risk sample. Future research investigating dispositional and contextual moderators of oxytocin response in addition to the therapeutic effects of more intensive oxytocin dosing or administration strategies on alcohol craving and aggression is warranted. Highlights: We examined 40 IU oxytocin to mitigate alcohol craving and IPA. We used validated alcohol cue and IPA laboratory paradigms. Findings support the safety/tolerability of oxytocin in a high risk sample. Hypotheses were not supported, but oxytocin was not aggressogenic.